Berkeley's Gland Tour into Speculative Fiction Part 2: Margaret Cavendish and Berkeley's Attitudes Towards Women - Moriarty, Clare (My University, 2023)
In Part 1, we explored how Berkeley drew from Homeric literature and used literary techniques such as satire to challenge his “freethinking” philosophical opponents in “The Pineal Gland” story published in The Guardian in 1713. Echoing the grand tours Berkeley undertook in subsequent years, Part 1 and 2 both present a “gland tour” of some motivations, influences and legacies of Berkeley's text. In particular, Part 2, explores a line of literary influence beginning with Margaret Cavendish and extending through Gabriel Daniel, Berkeley and Alexander Pope. In doing so, we present anticipations of features of Berkeley's story in the writings of Margaret Cavendish amid a discussion of Berkeley's complex attitudes towards women. The paper also argues that Berkeley's story represents an underappreciated yet significant milestone in the history of speculative fiction.
Keywords: Berkeley; Margaret Cavendish; Women